Comparison Analysis Of Fuel On Manual And Systematic Flight Plan On Citilink Airlines On The Jakarta-Surabaya Route Using Airbus A320 Aircraft - Mubarok, Ahmad; Tirtanto, Jadon Pieter Elia; Setiawan, Ariyono; Rumani, Daniel Dewantoro (Journal Research of Social Science, Economics, and Management, 2023)
A Flight Plan is an essential element for achieving efficiency. Prior to operating a flight, a Flight Plan must be prepared. The flight operations officers (FOOs) utilize Airbus's NavBlue application to create a systematic Flight Plan. They can also manually generate a Flight Plan using the FCOM (Flight Crew Operating Manual) guidebook. This research focuses on the differences in fuel planning between the systematic and manual methods of Flight Plan creation, as there are variations between the two approaches. Qualitative methodology is used to gather and analyze secondary data, including both manual and systematic Flight Plans, weather and environmental data, as well as aircraft technical documents and fuel tank capacities. The anticipated outcome of this research is to provide valuable insights for the aviation industry in enhancing operational efficiency.